2022
DOI: 10.3390/su14052509
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Hotel Employees in the Greater Accra Region of Ghana

Abstract: This study examines the effect of the COVID-19 pandemic on hotel employees in the Greater Accra Region of Ghana using the conservation of resource and human relations theories to ascertain the level of impact. Data was collected from 511 hotel employees from 58 hotels using questionnaires. The employees were randomly sampled. Stepwise Regression in Statistical Package for Social Sciences version 16 model was used to run the analysis. Nine independent variables were included in a stepwise regression model. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…This study corroborates with that of Shapoval et al. (2021) and Hervie et al. (2022) on the impact of COVID-19 on the hotel business in three nations, the United States of America, Sweden, and Israel.…”
Section: Findings and Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…This study corroborates with that of Shapoval et al. (2021) and Hervie et al. (2022) on the impact of COVID-19 on the hotel business in three nations, the United States of America, Sweden, and Israel.…”
Section: Findings and Analysissupporting
confidence: 88%
“…Also, in order to ascertain the effects of the COVID-19 pandemic on hotel personnel in the Greater Accra Region, Hervie et al (2022) study was motivated by the theories of "resource conservation and human resource management". According to their argument, stress is a factor in the notion of resource conservation.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, the turnover of employees was very high, especially in the private sector, which decreased organizational trust, especially in the tourism industry. Hervie et al (2022) have shown that one of the behaviors helps the hotel industry to face the pandemic was to minimize the number of employees. Worldwide, it was reported that 62 million jobs were lost in the tourism sector (ILO, 2021).…”
Section: Organizational Trustmentioning
confidence: 99%
“…They announced that 15.3 million tourism workers were affected by the COVID-19 pandemic of which 6.4 million were women (ILO, 2021). Hervie et al (2022) studied the effect of the COVID-19 pandemic on hotel employees in Ghana. More than 80% of the sample reported the effect on their salaries, while a wide percentage reported the threat to their jobs through the pandemic.…”
Section: Introductionmentioning
confidence: 99%